Family and Health Workers Support Influence Self-Regulation Based on Spirituality in Hypertension Patient - Riza Fikriana (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Self-regulation in hypertensive patients is very important to improve self-care abilities.Aim: The research objective was to analyze the effect of social support on self-regulation based on spiritualityin hypertension patients.Method: The research design was analytic observational. A sample of 56 hypertension patients was taken bysimple random sampling technique. The variables measured were social support and cell-regulation basedon spirituality. The research instrument was a questionnaire. Data were analyzed using a linear regressiontest.Result: The results showed that peer support and health workers were mostly in the moderate category at57.1% and 44.6%. Meanwhile, family support is mostly still lacking (75%). Self-regulation based on dailyspiritual experience has the highest mean value of 3,696. The linear regression analysis showed that socialsupport in the form of family support and support from health professionals had a significant effect on selfregulationbased on spirituality.Conclusion: Self-regulation based on spirituality is influenced by family and health worker support.